Spatio-Temporal Analysis of NO2 and CO Production with Sentinel 5P Tropomy Time Series Images: The Case of Torbalı and Kemalpaşa Districts of Izmir Province in Türkiye - Münevver Gizem Gümüş, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Air pollution is an environmental problem that seriously impacts human health and ecosystems and is associated with anthropogenic sources such as industry, traffic, and fossil fuel use. Nitrogen dioxide (NO₂) and carbon monoxide (CO) are the main air pollutants that cause respiratory diseases and contribute to climate change. This study combines Sentinel-5P TROPOMI satellite data with local air quality monitoring data provided by the National Air Quality Monitoring Network (UHKIA) of the Turkish Ministry of Environment, Urbanization, and Climate Change to perform a spatial and temporal analysis of NO₂ and CO emissions in the Kemalpaşa and Torbalı districts of Izmir, Türkiye. For the 17 months between January 2022 and July 2023, analysis using the Google Earth Engine (GEE) platform revealed that emission concentrations increase in winter months due to industrial activities and domestic heating and decrease in summer months due to reduced traffic density and meteorological conditions. It was observed that CO emissions spread over a wider area, while NO₂ emissions are concentrated in industrial and traffic-oriented regions. Accuracy analyses between satellite and UHKIA data showed a general agreement, but small deviations were recorded due to atmospheric effects and resolution differences. These analyses emphasized the importance of the integrated use of satellite and ground data in air pollution monitoring. The results provide a valuable scientific basis for local governments and policymakers for air quality management and strategic decision-making, especially in the Kemalpaşa and Torbalı districts.
Keywords: Air Quality; CO; Google Earth Engine; NO₂; Remote Sensing; Sentinel 5P